Isolation and partial characterisation of PHT1;5, a putative high affinity phosphate transporter from Arabidopsis thaliana - Loedolff, Bianke (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.